Morphological and physiological variation between queens and workers of Protonectarina sylveirae (de Saussure) (Hymenoptera, Vespidae, Epiponini) - Tanaka Junior, Getulio Minoru [UNESP]; Soleman, Raduan Alexandre [UNESP]; Noll, Fernando Barbosa [UNESP] (Sociedade Brasileira de Entomologia, 2010)
As vespas enxameadoras neotropicais, Epiponini, apresentam desde ausência de diferenciação morfológica entre as castas até castas altamente distintas. Medimos oito partes corporais das fêmeas de duas colônias de Protonectarina sylveirae (de Saussure, 1854). ANOVA e Análise Discriminante evidenciaram diferenças significativas entre as castas, como observado anteriormente por outros autores em outros Epiponini. No entanto, algumas fêmeas, previamente categorizadas como rainhas, eram na verdade operárias, com base nas análises estatísticas. Esses indivíduos apresentaram características morfológicas intermediárias entre rainhas e operárias, tendo padrões distintos de pilosidade e da marca do clípeo. As castas em P. sylveirae são distintas, no entanto indivíduos intermediários podem ser encontrados nas colônias promovendo uma flexibilidade social.

Morphological and physiological variation between queens and workers of Protonectarina sylveirae (de Saussure) (Hymenoptera, Vespidae, Epiponini). The Neotropical swarm-founding wasps, Epiponini, range from the absence of morphological differentiation between castes to highly distinct castes. We measured eight body parts of females of two colonies of Protonectarina sylveirae (de Saussure, 1854). ANOVA and Discriminant Analysis evidenced significant differences between castes, as previously observed by other authors for other species of Epiponini. However, some females previously categorized as queens, were actually workers, supported by our statistic analyses. These individuals showed intermediate morphological features between queens and workers, having distinct patterns of hairs and clypeal spots. The castes of P. sylveirae are distinct, however intermediate individuals may be found in colonies promoting social flexibility.
Variações morfológicas e fisiológicas entre rainhas e operárias de Protonectarina sylveirae (de Saussure) (Hymenoptera, Vespidae, Epiponini)
Keywords: Caste differentiation; Polistinae; Social wasp; Diferenciação de castas; Polistinae; vespas sociais